Peran Program Pojok Baca Terhadap Minat Baca Siswa Kelas V B SDN 1 Anyar - Dianawati Dianawati; Rauhun Jannah; Ana Mulyono (Asosiasi Riset Ilmu Pendidikan Indonesia, 2024)
This study aims to determine the role of the reading corner program on the interest of class VB students at SDN 1 Anyar. This research used a descriptive qualitative approach. The location of this research was SDN 1 Anyar Bayan. The subjects in this study were VB grade students with a total of 39 people with 22 males, and 17 females. Data collection techniques used observation, interviews and documentation. In this study, the authors used the Miles and Huberman model of data analysis. The researchers used to test the validity of the data is by triangulation. The result of this study is that the role of the reading corner program in increasing students' interest in reading in class VB SDN 1 Anyar. The reading corner plays a very important role in filling students' vacant time. This is done in order to socialize to students that reading is very important, then the teacher also invites students to read in the reading corner, especially if there are students who feel there are difficulties in learning, then the teacher directs students to the reading corner and looks for books related to the lesson, and requires students to participate in reading activities for 15 minutes at the beginning of the lesson.